2006
DOI: 10.1007/s00403-006-0713-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on wound-healing: a new perspective for wound-therapy?

Abstract: Wound healing is a complex regeneration process, which is characterised by intercalating degradation and re-assembly of connective tissue and epidermal layer. The pH value within the wound-milieu influences indirectly and directly all biochemical reactions taking place in this process of healing. Interestingly it is so far a neglected parameter for the overall outcome. For more than three decades the common assumption amongst physicians was that a low pH value, such as it is found on normal skin, is favourable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
662
0
22

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 860 publications
(697 citation statements)
references
References 25 publications
13
662
0
22
Order By: Relevance
“…8 E and Fig. S2), which suggests cellular metabolic adaptation to trauma-induced tissue hypoperfusion and hypoxia (Schneider et al, 2007). In the z-projection (14 optical sections of 10 µm) of the dermis between the perilesion area and the wound, a significantly higher colocalization (Supplemental material).…”
Section: Interaction Of Ptx3 With Fibrin and Plasminogen At Acidic Phmentioning
confidence: 85%
See 1 more Smart Citation
“…8 E and Fig. S2), which suggests cellular metabolic adaptation to trauma-induced tissue hypoperfusion and hypoxia (Schneider et al, 2007). In the z-projection (14 optical sections of 10 µm) of the dermis between the perilesion area and the wound, a significantly higher colocalization (Supplemental material).…”
Section: Interaction Of Ptx3 With Fibrin and Plasminogen At Acidic Phmentioning
confidence: 85%
“…Liver injury. Mice (129/Sv) were injected s.c. with 50 µl/20 g of carbon tetrachloride (CCl 4 ) dissolved in a 1:1 ratio with mineral oil (Sigma-Aldrich), as pH ranging from 5.5 to 6.9 occurs at sites of tissue injury (Schneider et al, 2007) and in growing tumors (Gatenby and Gillies, 2004). The Plg activators uPA and tPA are neutral proteases (Hamilton, 1980) and accordingly, we observed that cellfree fibrinolysis was less effective at acidic pH compared with neutral pH.…”
Section: Animal Modelsmentioning
confidence: 95%
“…In the environment of a tumor or wound bed, it is well established that the extracellular pH can become acidic. [80][81][82] In the tumor environment, the measured pH values range from 5.85-7.68. 81 Early stage wounds have a measured average pH of 5.7-6.1.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…With this acquired sensory information, possible complications typically resulting from infections of the wound, can be treated promptly so that penetration of pathogens into the body and the bloodstream can be avoided. Inflammation is a complex cellular process that changes the properties of the wound exudate and alters various physiological parameters like; pH [1], temperature [2][3], wound humidity or viscosity [4][5], concentration of various ions (particularly reactive oxygen species) [6][7] and content of lactate [8][9] or urea [10][11]. Therefore, the wound healing process can be assessed by continuous monitoring of one or more properties.…”
Section: Introductionmentioning
confidence: 99%
“…The pH value plays an important role in the wound healing process and the precise relationship between the pH value and the condition of the wound depends on the wound type. Generally, it can be said that a permanent pH-value higher than 7.5 over a long period, is an indicator of impaired wound healing [1].…”
Section: Introductionmentioning
confidence: 99%